2019
DOI: 10.1175/bams-d-17-0152.1
|View full text |Cite
|
Sign up to set email alerts
|

A Transformational Approach to Winter Orographic Weather Modification Research: The SNOWIE Project

Abstract: The Seeded and Natural Orographic Wintertime Clouds: The Idaho Experiment (SNOWIE) project aims to study the impacts of cloud seeding on winter orographic clouds. The field campaign took place in Idaho between 7 January and 17 March 2017 and employed a comprehensive suite of instrumentation, including ground-based radars and airborne sensors, to collect in situ and remotely sensed data in and around clouds containing supercooled liquid water before and after seeding with silver iodide aerosol particles. The se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 58 publications
1
54
0
Order By: Relevance
“…Recent results from the SNOWIE field campaign about winter orographic clouds and precipitation [48] found a frequent decoupling between the orographic cloud layer where precipitation was formed and the near-surface air layer, which was trapped at the bottom of the valley. In our study, we also find a decoupling between ground-level conditions and higher levels but affecting precipitation profiles as well.…”
Section: Discussionmentioning
confidence: 99%
“…Recent results from the SNOWIE field campaign about winter orographic clouds and precipitation [48] found a frequent decoupling between the orographic cloud layer where precipitation was formed and the near-surface air layer, which was trapped at the bottom of the valley. In our study, we also find a decoupling between ground-level conditions and higher levels but affecting precipitation profiles as well.…”
Section: Discussionmentioning
confidence: 99%
“…The SNOWIE and CAMPS campaigns Data for this study were drawn from two field campaigns, both set in the intramountain, western United States. The first and most recent project, Seeded and Natural Orographic Wintertime Clouds: The Idaho Experiment (SNOWIE), was launched in order to address questions pertaining to both natural and seeded orographic clouds (Tessendorf et al 2019). SNOWIE took place between 7 January and 17 March 2017 in the Payette basin northeast of Boise, Idaho (Fig.…”
Section: Observational Campaigns Instrumentation Andmentioning
confidence: 99%
“…1a). Tessendorf et al (2019) describe the complete SNOWIE experimental design, project domain, and observed cloud and precipitation properties. The experimental design did not consider KH waves; their prevalence in all stratiform precipitation systems sampled during SNOWIE came as a surprise, and led to the questions that motivated this study.…”
Section: Observational Campaigns Instrumentation Andmentioning
confidence: 99%
“…The various seeded ensemble members investigated here attempt to capture this uncertainty, recognizing that more research is needed to have full confidence in the scheme. The recent Seeded and Natural Orographic Wintertime Clouds: The Idaho Experiment (SNOWIE) project (French et al 2018;Tessendorf et al 2018) was largely motivated to reduce this uncertainty, and data from this field program is currently being analyzed and used to evaluate and improve the seeding algorithm.…”
Section: A Description Of Ensemble Modeling Approachmentioning
confidence: 99%
“…This would require specific field studies for both ground and airborne seeding. The recent SNOWIE field effort (Tessendorf et al 2018;French et al 2018) has provided an excellent dataset for such an evaluation.…”
Section: A Next Stepsmentioning
confidence: 99%